The relationship between Malaysian university lecturers’ conceptions of Assessment Practice: Hubungan konsepsi pensyarah universiti di Malaysia terhadap Amalan Pentaksiran - Hassan , Noor Asiah; Che Md Ghazali , Nor Hasnida; Idris, Izazol; Mohd Hassan , Rodiah; Man, Emilia (Jurnal Pendidikan Bitara UPSI, 2023)
This study was conducted to identify the level of university lecturers’ conception of assessment and their practices towards assessment in Malaysia. The relationship between conception and the implementation of assessment practices by lecturers was also examined. The study employed a quantitative approach with cross-sectional time frame and involved a total of 382 respondents that consist of university lecturers in Malaysia. Multistage sampling technique was used in data collection. The survey instrument used in this study was adapted from two previous studies (COA-III and APIM). The data were analyzed descriptively using the Statistical Package for the Social Sciences (SPSS) version 26, while structural equation modeling and model fit tests were conducted using IBM SPSS AMOS version 24. The findings of the study indicated that the level of conception and the practice of assessment among lecturers were high. The analysis using Structural Equation Modeling revealed that conception significantly influenced lecturers’ assessment practices which explaining 33% of the total variance through conception. In conclusion, the findings of this study can serve as a guide for the stakeholder in optimizing the level of assessment practices among lecturers through improving their conception of assessment.